Alejandro y la Anábasis de la medicina griega - Antela Bernárdez, Borja, 1977-; Sierra Martín, César (2016)
This paper is focused on the role of classical Greek medicine in the expedition of Alexander the Great. We will focus on the medical care and its role in health crises context. We conclude that Alexander's army tried to that many soldiers had access to medical care in complex health situations, especially in India. Finally, we think that the Anabasis of Alexander was a great experience for Greek medicine and a first step in the formalization of the doctor in the army.
Keywords: Alejandro Magno; Medicina griega y romana